You are on page 1of 17

Successive Differentiation

Leibnitz Rule

Solved Problems

Leibnitzs Rule :-

Q} If y = uv
y = x2excosx
Find yn = ?
Soln:Let u = excosx , v = x2
yn = exrn cos(x+n) x2 + nexrn-1 cos(x+(n-1)) (2x) +
()

cos(x+(n-2)) 2
!
where r =
= () =
Q} y =

P.t. y5 =

+ +
{ 1+

+ logx}

Soln:() ()!

Let u = logx
un =

v =
y5 = u5v + 5u4v1 + 10u3v2 + 10u2v3 +5u1v4 + uv5
!

= { +

( ) + {

+ + + }

( ) + ( ) ( ) +

Successive Differentiation

Leibnitz Rule

Solved Problems

Q} If In = { }
P.t In=nIn-1 + (n-1)!
Also P.t In=n! {logx + 1 + +. . . .+ }

Soln :- In = { }

= { ( . )}

= { + () }

= {
+ ( . )
In= ( ) +

! =

()!

Put n= 1,2,3,.

= +
!

()

()

= () +

()!

= +

()

( )

Adding

+
!

+
!

()!

+ +
!

()!

()!

+
!

+ + ++
+

= ! + + + + +

= logx + + + + +

++

Successive Differentiation

Leibnitz Rule

Solved Problems

Q) If y =
!
+ =
Soln :y =

= +
= +
i.e. = +
Using leibintz theorem
{+ + } = n! +
+ = !
!
+ =
Q) If x+y = 1

P.t. ( ) = ! { (nC1)2 + (nC2)2 +


+ (nCn)2 () }
Let u =
v = = ( )
= ( ) () = ()
= ( )( ) () = ( ) ()
= ! ()
=
= ( )
3

Successive Differentiation

Leibnitz Rule

Solved Problems

= !

( . ) = (nC0) n! + (nC1)n! () + (nC2)

() ( ) + . . + (nCn) n!()

= n!{ (nC1)2 +( nC2)2 + +


() (nCn)2}

Q) If =
. . () nC2 ()+ nC4 () + =
y=

ycosx = sinx
By leibintz Rule
() + nC1 + ()() + nC2 ()() +
n
C3 ()() +
n

C4 ()() + = ( +

Put x = 0
() nC2 ()+ nC4 () + =

Successive Differentiation

Leibnitz Rule

Solved Problems

Q) If y =
= ( )
Hence P.T ( ) (( ) + ) (
)( ) =
Soln:- =

()

2y =

()()(+)()

2y =

()

()

()

() (

+
)

()

y = ( )
i.e ( ) =
By leibnitz rule taking (n-1)th derivative
= { ( ) + ( ) () +
()()
!

() } =

( ) ( + + ) ( )(
) =
5

Successive Differentiation

Leibnitz Rule

Solved Problems

Q) If y = cos(m )
P.T. ( ) ( + ) + ( ) =
Soln: = sin(m )

( ) = (m )
( ) +

()

= m cos(m )

( ) =
( ) + =
By leibints theorem
{+ ( ) + + () +
{ + + } + =

()

()}

+ ( ) + + ( ) +( ) =
+ ( ) ( + )+ + ( ) =

Q) If

P.T ( )+ + ( + )+ +( ) =
Soln:

=
6

Successive Differentiation

Leibnitz Rule

+ =

Solved Problems

+ =0

=
y = ( )
= ( ) { +

= ( )

= = (
)
( ) + =
Using Leibnitz theorem
{+ ( ) + + () +
} =

()

()} + {+ +

( )+ + (2n+1)x+ + ( ) =
Q) If x = cos
=
(1- )+ ( + )+ ( + ) =
logy = m
y =
7

Successive Differentiation

y =
=

Leibnitz Rule

Solved Problems

=
()

+ =

( ) =

Q) If y =

P.T

(
+

)+(2n+3)x+ + ( +
+

) =
y( + ) = ( + + )
Take 2 derivatives and apply Leibnitz rule
( + ) +

Successive Differentiation

Leibnitz Rule

Solved Problems

Q) If u = f(x)
y =
P.T = ( + )


n
= nC0 + nC1
(. ) + C2 ( . ) +
+ nCn ( . )

= { nC0 + nC1 + nC2 + + nCn


}
= ( + )

(1) If y = x2 e2x P.T. yn = 2m2 m(n 1)


Soln.:

= x2 e2x

By Leibnitz's theorem,
Note : Take vas that function whose derivative vanish
after some derivative.
= (x2e2x)m

ym
= (e2x)m x2 + (e2x)m1 (x2)1 +
= 2me2x x2 + m2 m1 e2x

x+

m(m 1)
2

2n2

ex

2+0

ym (0)

= 0 + 0 + m(m 1)
2

2m2, e0 2

Successive Differentiation

Leibnitz Rule

Solved Problems

= 2m2 m (n 1)

ym (0)

(2) If y = x log (x + 1) prove that : ym = (1)


Soln.:

m 2

(m 2 )! ( x m )
( x 1 )m

x log(x 1)

By Leibnitz's theorem,
= x log(x 1)

ym

ym

= log(x 1)

ym

ym

(1)m 1 (m 1)!
m (1)m 2 (m 2)!
x

1 0
(x 1)n
(x 1)n1

ym

x m log(x 1)m 1 (x )1 ....

(1)m 2 (m 2)!
(1)(m 1)x m (x 1)
(x 1)m

10

(1)m 2 (m 2)!(x m )
(x 1)m

Successive Differentiation

Leibnitz Rule

(3) If y = xm log x P.T. ym+1 =


Soln.:

Solved Problems

m!
x

y = xm log x
1
x

y1 = mxm1 logx + xm

Note :
Since we want ym+1 so first find y1 and then take
the mth derivative.

xy1 = m xm log x + xm

xy1 = my + xm

Now on differentiating n times and by using Leibnitzs


theorem we have,

(x, y1)m = (ny)m + (xm)m

ym+1 x + m ym 1 = mym + m !

ym+1 =

m!
x

(4) If f () = cot show that n


Soln.:

f () cot

c1

f n 1 () nc 3 f n 3 () nc 5 f n 5 ().... cos

n
2

cos
sin

f () sin = cos
Now on differentiating n times and by using Leibnitzs
theorem we have,
f () sin cos
n

f n () sin nc f n 1 () cos nc f n 2 ()( sin )


1

11

Successive Differentiation

Leibnitz Rule

Solved Problems

nc f n 3 ()( cos ) .. cos

put = 0,
0 nc1 f n 1 (0) 0 nc 3 f n 3 (0)... cos

n
2

n
2

nc1 f n1 () n(3 f n3 ().... cos

(5) If w = tan (logy)or y = etan1(w)


prove that : (1 + w2)yn+1 + (2nw 1)yn n (n 1) yn1 = 0
y = etan1 (w)

Soln.:

y1 = etan1(w)

(1 + w2)y1 = y

1
1 w2

y
1 w2

Now on differentiating n times and by using Leibnitzs


theorem we have,

(1 w)y1 n y n

y n 1 (1 w 2 ) n y n (2w)

1 w 2 )y n1 (2nw 1)y n n(n 1)yn 1

(6) If

x sin , y sin 2 prove

Soln.:
y1 =

that (1 x

y sin 2 2 xin cos

y=

Note :

n(n 1)
y n 1 (2) 0 y n
2

2x 1 x 2
2 1 x 2 2x

cos =

(2 x )
2 1 x2

1 sin 2

1 x 2 y1 2(1 x 2 ) 2 x 2
12

) y n 2 (2 n 1 ) xy n 1 (n 2 4 ) y n 0

Successive Differentiation

Leibnitz Rule

Solved Problems

1 x 2 y1 2 4 x 2

on differentiating w.r.t. x,
y 2 1 x 2 y1

2
8 x
2 1 x2

(1 x 2 )y 2 xy 1 8 x 1 x 2

(1 x 2 )y 2 xy 1 4 y

(1 x 2 )y 2 xy 1 4 y 0

Now on differentiating n times by using Leibnitzs


theorem we have,

(1 x

1 x y

n 2

n(2 x )y n1

1 x y

n 2

2nxy n1 n(n 1)yn xy n1 nyn 4 yn 0

1 x y

n2

(2n 1)xy n1 [n 2 n n 4 ]yn 0

1 x y

n2

(2n 1)xy n1 (n 2 4 )yn 0

)y 2 n xy 1 n 4 y n 0

n(n 1)
(2) yn xy n1 2ny n 4 y n 0
2

13

Successive Differentiation

Leibnitz Rule

Solved Problems

(7) If y = A cos (log x) + B sin (log x)then show that


x2yn+2 + (2n +1)xy
constant.
Soln.:

y=

n+1+

(n2 +1)n = 0 where A and B are

A cos(log x ) B sin(wgx )

y1 = A sin(log x ) B cos(log x )
x

xy1 =

A sin(log x ) B cos(log x )

on differentiating w.r.t. x,
Aws (log x ) B sin(log x )

x
x

xy2 + y1 =

x2y2 + xy1 = Aws (log x ) BSin (log x )

x2y2 + xy1 = y By (1)

Now on differentiating n times by using Leibnitzs


theorem we have,

x y x, y y
2 2

x 2 y n 2 n(2 x )y n1

n(n 1)
2 y n1 ny n y n
2

x 2 y n2 (2n 1)xy n1 n(n 1) n 1y n 0

xy n 2 (2n 1)xy n1 (n 2 1)y n 0

(8) If y =

log( x x 2 1 )

prove that

y2m (0) = 0 and y2m+1 (0) = (1)m, 12, 32, 52 (2m 1)2
Soln.:

y log(x x 2 1 )
y1

y1

2x
1

2
x x 1
2 x 1
1

1
x2 1
14

Successive Differentiation

Leibnitz Rule

Solved Problems

x 2 1 y1 1

on differentiating w.r.t. x we have,


x 2 1 y 2 y1

2x
2 x2 1

=0

(x 2 1)y 2 xy 1 0

Now on differentiating m times by using Leibnitzs


theorem we have,
(x

x
at

1)y m 2 m (2 x )y m 1

m (m 1)
2 y m xy m 1 my m 0
2

1 ym 2 (2m 1)xy n1 m 2 y m 0

x = 0, y (0) = 0, y1(0)= 1, y2(0)= 0 ym+2(0) = m2ym(0)

To find y3 (0)Put m = 1 in
y12 (0) y 3 (0) 1 2 y1 (10 ) (1)1 1 2

m 2, y 2 2 (0) y 4 (0) 2 2 , y 2 (0) 0


m 3 y 3 2 (0) y 5 (0) 3 y 3 (0) 3 2 1 2 (1)2 1 2 3 2

= (1)

1 2 (2 2 1)2 )

y m(0) 0
2

and
(9) If

y 2 m 1 (1)m 1 2 ,3 2....( 2m 1)2

or if p =sin1x = sin1y prove that


(2 n 1 ) xy ( p n ) y 0 and hence de duce yn(0) =

y sin( p sin 1 x )

(1 x 2 ) y n 2

n 1

0
if n is even and yn(0) = .(32 p2)p (n2)2 p2 if n is add
where p is any constant.
Soln.:

y sin( p sin 1 x )

15

Successive Differentiation

Leibnitz Rule

y1 cos( p sin 1 x )

Solved Problems

p
1 x2

1 x 2 y 1 p(p sin 1 x )

[ cos2 + sin2 =

(1 x 2 )y 2 p 2 (1 y 2 )

1]
Now on differentiating n times by using Leibnitzs
theorem we have,
(1 x 2 )2 y1 y 2 y1 (2 x ) p 2 (2 yy 1 )(1 x 2 )y 2 xy 1 p 2 y
2

(1 x 2 )y n2 ny n1 (2 x )

n(n 1)
y n (2) y n1 , x ny n p 2 y n
2

(1 x 2 )yn 2 (2 x 1)xy n1 (p 2 n 2 )yn 0

at x = 0,

y (o) = sin (p sin1(o) = sin (p


y1 (o) = cos (psin1x

p
1 02

y 2 (o) p 2 y(0) 0
y n 2 (o ) (n 2 p 2 )yn(o )

If n=1,

y 3 (o) (12 p 2 )y, (o) (12 p 2 )p

n=2,

y 4 (o) (2 2 p 2 )y 2 (o) (2 2 p 2 )o 0

n=3,

y 5 (o) (3 2 p 2 )y 3 (o) (3 2 p 2 )(12 p 2 )p

16

o) = o
=p

Successive Differentiation

Leibnitz Rule

Solved Problems

yn (o) o

yn (o) (n 2)2 p 2 ....( 3 2 p 2 )(12 p 2 )p

(10) If

p x
p x

tan1

( p 2 x 2 ) yn 2 2 (n 1 ) xy n 1 n(n 1 ) y n

prove

that

where p is any constant.

p x
y tan 1

p x

Soln.:

put x = p tan

y=

p p tan
1 tan
tan 1
tan 1

1 tan
p p tan

y=

tan 1 tan

x
tan 1 ( )
4
4
p

1
1
p
2
2
x p p x2
1 2
p

on differentiating w.r.t. x we have,

(p2 +x2)y2 + y1 (2x)= 0

Now on differentiating n times by wing Leibintzs


theorem we have,

(p

x 2 )y 2

2 xy
n

1 n

n(n 1)
2 yn 2 x y n1 n 2 y n 0
2

( p 2 x 2 )y n 2 (2 x ) y n 2

( p 2 x 2 )y n 2 2(n 1)x y n 1 [n(n 1) 2n]y n 0

( p 2 x 2 )y n2 2(n 1)xy n1 n(n 1)y n 0

17